Computational engineering: mathematical models in heat flow dynamics study. - Gago, Eduardo Alberto; D’Alessandro, Lucas Iván; Zurbriggen, Marcelo M. (WSEAS, 2022)
According to the latest educational innovation trends in engineering, new teaching paradigms emerge to achieve higher development in intellectual capacities, acquisition of skills, substitution of outdated techniques for more efficient and fast means, and a better integration of knowledge in the teaching and learning processes. In line with these paradigms, we have set up new pedagogic methodologies together with computer resources to work with the development of functions with a complex variable and Laplace transform from a multidisciplinary view in the subject Advanced Calculus of the Mechanical Engineering Programme. The didactic proposal presented is about systems related with heat transfer in a fluid where the concepts used in the models are approached analytically and graphically making the curricular content meaningful and facilitating the interpretation and conceptualization of the theory.
Keywords: Ingeniería mecánica; Enseñanza de la matemática; Cálculo avanzado; Recursos educativos; Tecnologìa de la educación